COVID-19 and the climate emergency : do common origins and solutions reside in the global agrifood system? - Horton, Benjamin Peter (2022)
The coronavirus disease 2019 (COVID-19) pandemic and the climate emergency are devastating symptoms of the unsustainability of human society and the decreasing resilience of an unhealthy planet. Here, we discuss whether both COVID-19 and the climate emergency have the same underlying causes, and therefore common solutions, and whether they are rooted in a failing global agrifood system.